2015
DOI: 10.1111/imj.12684
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of aminoglycoside dosing and estimated glomerular filtration rate in determining gentamicin and tobramycin area under the curve and clearance

Abstract: Current guideline dosing may be suboptimal for achieving target area-under-the-curve. The CKD-EPI equation adjusted for patient body surface area best predicts aminoglycoside clearance, and could be evaluated as a covariate in determining initial aminoglycoside dosing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…In contrast to tobramycin, renal function estimates (eGFR or GFR based on 24-h urine collection) were inferior to TBW in predicting gentamicin clearance, despite the fact that in both studies individuals with a similar distribution in body weights and renal function (all >60 ml/min) were included. Interestingly, this finding has been reported before by other studies, describing stronger correlations between eGFR and drug clearance for tobramycin than gentamicin ( 15 , 29 ). To explain this difference between tobramycin and gentamicin, it could be hypothesized that transporters play a role.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In contrast to tobramycin, renal function estimates (eGFR or GFR based on 24-h urine collection) were inferior to TBW in predicting gentamicin clearance, despite the fact that in both studies individuals with a similar distribution in body weights and renal function (all >60 ml/min) were included. Interestingly, this finding has been reported before by other studies, describing stronger correlations between eGFR and drug clearance for tobramycin than gentamicin ( 15 , 29 ). To explain this difference between tobramycin and gentamicin, it could be hypothesized that transporters play a role.…”
Section: Discussionsupporting
confidence: 88%
“…The influence of obesity on aminoglycoside clearance has been reported in some studies over the years ( 11 13 , 15 , 16 , 29 ). Although in general these studies found an increase in clearance with increasing body weight, their results have to be interpreted with caution since individuals in most of these studies were only moderate obese compared to present-day standards with average body weights around 85–105 kg with standard deviations of ±12–18 kg ( 12 , 13 , 16 ).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Studies with aminoglycosides, compounds that serve as excellent probes of glomerular filtration, have verified that the CKD-EPI equation is likely to be more precise than either the C-G or MDRD equations. 35,36 The CKD-EPI equation has also been shown to be relevant for stratification of risk when dosing edoxaban in patients with good renal function. 37 Also, the CKD-EPI estimate of renal function led to concordant dosing recommendations of antiretroviral dosing in a French cohort of patients with HIV.…”
Section: The Fork In the Roadmentioning
confidence: 99%
“…The CKD‐EPI equation has demonstrated utility in predicting drug pharmacokinetics and informing dosing. Studies with aminoglycosides, compounds that serve as excellent probes of glomerular filtration, have verified that the CKD‐EPI equation is likely to be more precise than either the C‐G or MDRD equations . The CKD‐EPI equation has also been shown to be relevant for stratification of risk when dosing edoxaban in patients with good renal function .…”
Section: The Fork In the Roadmentioning
confidence: 99%